2007
DOI: 10.1002/cne.21232
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and thalamic connections of the representations of the teeth and tongue in somatosensory cortex of new world monkeys

Abstract: Connections of representations of the teeth and tongue in primary somatosensory cortex (area 3b) and adjoining cortex were revealed in owl, squirrel, and marmoset monkeys with injections of fluorescent tracers. Injection sites were identified by microelectrode recordings from neurons responsive to touch on the teeth or tongue. Patterns of cortical label were related to myeloarchitecture in sections cut parallel to the surface of flattened cortex, and to coronal sections of the thalamus processed for cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 111 publications
(148 reference statements)
2
57
0
Order By: Relevance
“…Thus the results of this study clearly indicate that periodontal afferents from the first upper left incisor project to both contra-and ipsilateral SI cortices via the trigeminothalamic tract and that the projection from the contralateral ascending pathway is dominant. This is in agreement with earlier findings based on recording somatosensory-evoked magnetic fields during intraoral tactile stimulation (excluding the teeth) in humans (Tamura et al 2008) and from neuronal tracing studies (teeth and tongue) in new world monkeys (Iyengar et al 2007). Previous studies have reported locations in the SI cortex for intraoral structures including the lip, hard palate, gingiva, and tongue (Murayama et al 2005;Nakahara et al 2004;Nevalainen et al 2006), tooth dental pulp (Kubo et al 2008), and tooth tactile stimulation (Miyamoto et al 2006), but this is the first report of SI activations to psychophysically controlled vibrotactile stimulation of periodontal afferents.…”
Section: Brain Activation To 20 Hz Tooth Vibrationsupporting
confidence: 93%
“…Thus the results of this study clearly indicate that periodontal afferents from the first upper left incisor project to both contra-and ipsilateral SI cortices via the trigeminothalamic tract and that the projection from the contralateral ascending pathway is dominant. This is in agreement with earlier findings based on recording somatosensory-evoked magnetic fields during intraoral tactile stimulation (excluding the teeth) in humans (Tamura et al 2008) and from neuronal tracing studies (teeth and tongue) in new world monkeys (Iyengar et al 2007). Previous studies have reported locations in the SI cortex for intraoral structures including the lip, hard palate, gingiva, and tongue (Murayama et al 2005;Nakahara et al 2004;Nevalainen et al 2006), tooth dental pulp (Kubo et al 2008), and tooth tactile stimulation (Miyamoto et al 2006), but this is the first report of SI activations to psychophysically controlled vibrotactile stimulation of periodontal afferents.…”
Section: Brain Activation To 20 Hz Tooth Vibrationsupporting
confidence: 93%
“…The results are incompletely analyzed and only reported in the form of an abstract (Iyengar et al, 2002). Yet a few conclusions are well supported.…”
Section: Thalamic and Cortical Connections Of Teeth And Tongue 01 Andmentioning
confidence: 99%
“…This "hand-face border" can be detected as a myelin-light septum in brain sections cut parallel to the cortical surface. Further laterally, myelin-dense ovals were shown to indicate anatomical modules that correspond to representations of different orofacial structures in both New [16,17] and Old World monkeys [13,15]. In New World monkeys, the myelin-dense ovals are arranged in a rostrocaudal direction and extend to the ventral frontal lobe.…”
Section: Representation Of Orofacial Structures In Area 3bmentioning
confidence: 94%
“…Dense neural interconnections between representations of different orofacial structures have been documented in both New [17] and Old World monkeys [15]. For example, a recent neuroanatomical study of macaques [15] demonstrated that the tongue representation received dense projections from regions representing the lower and upper teeth and tissue lining the inside of the cheek and lips.…”
Section: Representation Of Orofacial Structures In Area 3bmentioning
confidence: 99%
See 1 more Smart Citation